Healthcare Preventive Measures, Logistics Challenges, and Corporate Social Responsibility During the Covid-19 Pandemic: Break the Ice - Sasmoko; Muhammad Saeed Lodhi; Abdul Rashid Bin Abdul Aziz; Nur Fatihah Abdullah Bandar; Rahimah Embong; Mohd Khata Jabor; Siti Nisrin Mohd Anis; Khalid Zaman (Emerald Publishing Limited, 2024)
Purpose: The study aims to analyze the role of coronavirus testing capacity to possibly reduce the case fatality ratio (CFR) in a large cross-section of countries. The study controlled health-care expenditures, logistics performance index (LPI), carbon damages, and corporate social responsibility (CSR) to understand the nature of causation between the CFR and stated factors.